Answers

2014-09-21T22:02:43+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
x = \frac{ \sqrt{a+2b}+ \sqrt{a-2b} }{\sqrt{a+2b}- \sqrt{a-2b} } \\ \\ = \frac{ (\sqrt{a+2b}+ \sqrt{a-2b})(\sqrt{a+2b}+ \sqrt{a-2b}) }{(\sqrt{a+2b}- \sqrt{a-2b})(\sqrt{a+2b}+ \sqrt{a-2b}) } \\ \\ = \frac{a+2b + a-2b + 2 \sqrt{a+2b}\sqrt{a-2b} }{a+2b - (a-2b)} \\ \\ = \frac{2a + 2\sqrt{a^2-4b^2}}{4b}\\ \\x\ =\ \frac{a + \sqrt{a^2-4b^2}}{2b}\\ \\

This is in the format of a root of a quadratic equation as : 
Roots\ of\ ax^2+bx+c = 0\ are\ x\ = \frac{-b +- \sqrt{b^2-4ac}}{2a} \\ \\

So use similarity:  a becomes -b;  c becomes a = -b   as,   4b² = 4 a c

So  -b x² + a x - b = 0

b x² - ax +b = 0

================================
Or, another way,

2 b x = a + √(a²-4b²)

(2bx-a)² = a² - 4b²
4b²x² +a² - 4abx = a² - 4b²
4b²x² - 4abx + 4b² = 0

divide by 4b

bx² - ax +b = 0

2 4 2
2014-09-22T12:07:57+05:30
See the attachment for the soln.

0